Telemedicine for educating parents or caregivers for postoperative care of pediatric patients: a systematic review - Vivas-Colmenares, Grecia Victoria; Ramírez-Iglesias, Jose Ruben; Martínez-Pérez, Ana M. (Frontiers in Public Health, 2025)
IntroductionTelemedicine reduces in-person appointments and extends healthcare services to rural areas. Despite its extended use after the COVID-19 pandemic, further analysis of educational applications and strategies is needed to better prepare parents and caregivers for postoperative pediatric care beyond routine clinical follow-up. Therefore, this review systematically evaluates the effectiveness of telemedicine interventions in educating parents or caregivers after pediatric surgery, with respect to caregiver knowledge and self-efficacy in postoperative care, caregiver satisfaction, and postoperative clinical outcomes.MethodsFollowing the PRISMA guidelines, we searched three databases, PubMed, Scopus, and LILACS, for articles published between 2013 and 2023 that involved patients aged 0–18 years who underwent surgery and caregivers who received some form of education through telemedicine. We evaluated the effectiveness of telemedicine for educational purposes by assessing caregiver knowledge, satisfaction, and patient morbidities. Bias was analyzed using the RoB2 and ROBINS-I tools. The certainty of the presented evidence was assessed using the GRADE guidelines. The SWiM guideline was employed to report a structured narrative synthesis from the combined results. The protocol was registered in the International Prospective Register of Systematic Reviews (CRD42024545858).ResultsFour studies were included from 2,163 records initially registered: two randomized controlled trials (RCTs) and two uncontrolled before–after (UCBAs) studies. In the RCTs, caregiver knowledge was significantly higher in the telemedicine intervention group (p < 0.05); in one UCBA, caregiver knowledge increased over time. All studies reported high satisfaction with telemedicine, with the RCTs showing significantly higher satisfaction levels than control groups (p < 0.05). One UCBA also reported a significant improvement in patient continence. Bias was assessed as moderate in the RCTs and high in the UCBAs. The GRADE criteria indicate a certainty of evidence moderate for satisfaction and caregiver knowledge, and very low for morbidity and rate of complications or adverse events.DiscussionTelemedicine-based educational tools show promise as a strategy for healthcare systems, achieving high acceptance levels. However, further research is required to refine the methodological approaches for implementing telemedicine in caregiver education within the postoperative setting.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024545858, identifier [CRD42024545858].